PSXI-4 Minimum inhibitory concentration of a heterotrophically grown, dried microalgae powder (All-G-Rich®️) and extracted microalgal oil against selected intestinal microorganisms. (7th December 2018) - Moran, C; Keegan, J; Jacques, K; Hart, H
Abstract: The influence of novel feed ingredients on the intestinal microbiota of food production animals is an on-going regulatory concern. An in vitro study was conducted to determine the minimum inhibitory concentration (MIC) of a heterotrophically grown, unextracted docosahexaenoic (DHA) acid-rich Aurantiochytrium limacinum (AURA) microalgae and the extracted oil from AURA algae on selected intestinal microorganisms. One strain of each of the following genera of intestinal bacteria (per VICH GL36(R)) was selected: Generic E. coli, and species of Bacteroides, Bifidobacterium, Clostridium, Enterococcus, Eubacterium (Collinsella), Fusobacterium, Lactobacillus, and Peptostreptococcus/Peptococcus ). MIC assays for the DHA-enriched algae and algae oil (extracted DHA) were conducted separately for each product against each selected microorganism using the 'broth macro-dilution' procedure for antibiotic susceptibility testing per NCCLS methods (National Committee for Clinical Laboratory Standards, USA) (i.e., 1:1 serial dilutions as follows: 1%, 0.5%, 0.25%, 0.125%, etc., through 0.0002441406%). The inoculum for each microorganism was prepared and the MIC assay conducted according to respective culture methods described by NCCLS (M7-A9, 2012). Positive and negative control tubes were also prepared. For both products, at concentrations of 1% through 0.0625%, turbidity was noted in the dilution suspensions prior to inoculation. Following incubation, turbidity was noted in each of the 13 tubes in the dilution series for E. coli ATCC ® 25922™, E. faecalis ATCC® 51299™, B. fragilis ATCC ® 25285™, B. longum ATCC ® 15707™, Cl. difficile ATCC ® 700057™, F. canifelinum ATCC ® BAA-689™, C. aerofaciens ATCC ® 29738™, P. anaerobius ATCC ® 27337™, and Lactobacillus brevis ATCC ® 14869™. No inhibition of the nine organisms tested ( E. coli, E. faecalis, B. fragilis, B. longum, C. difficile, F. canifelinum, C. aerofaciens P. anaerobius, or L. brevis ) was detected up to concentrations of at least 0.03125%, which suggests that inhibition does not occur at concentrations of up to 1% for both the AURA unextracted microalgae and extracted oil samples.